Discovery of Phosphonic Diamide Prodrugs and Their Use for the Oral Delivery of a Series of Fructose 1,6-Bisphosphatase Inhibitors - Dang, Qun; Kasibhatla, Srinivas Rao; Jiang, Tao; Fan, Kevin; Liu, Yan; Taplin, Frank; Schulz, William; Cashion, Daniel K; Reddy, K. Raja; van Poelje, Paul D; Fujitaki, James M; Potter, Scott C; et al. (Journal of medicinal chemistry, 2008)
Like most phosphonic acids, the recently discovered potent and selective thiazole phosphonic acid inhibitors of fructose 1,6-bisphosphatase (FBPase) exhibited low oral bioavailability (OBAV) and therefore required a prodrug to achieve oral efficacy. Syntheses of known phosphonate prodrugs did not afford the desired OBAV; hence, a new class of prodrugs was sought. Phosphonic diamides derived from amino acid esters were discovered as viable prodrugs, which met our preset goals: excellent aqueous stability over a wide pH range, benign byproducts (amino acids and low molecular weight alcohols), and most importantly good OBAV leading to robust oral glucose lowering effects. These desirable properties of phosphonic diamides represent significant improvements over existing prodrug classes. Optimization of the diamide prodrugs of phosphonic acid 2a (MB05032) led to the identification of diamide 8 (MB06322), the first reported orally efficacious FBPase inhibitor.